A MOVE ANALYSIS OF CONFERENCE ABSTRACTS IN APPLIED LINGUISTICS - PEDAGOGICAL IMPLICATIONS FOR TEACHING AND LEARNING ENGLISH FOR ACADEMIC PURPOSES - Phuong, Cao Thi Hong (VNU Journal of Foreign Studies; Vol 34 No 4DO - 10.25073/2525-2445/vnufs.4284, 2018)
This current paper presents the findings of move analysis of conference abstracts from the British Association for Applied Linguistics (BAAL). Reviewing different core perspectives of move analysis such as Biber et al. (2007); Swales (1981, 1990); Santos (1996), the paper employed suitable approaches namely Biber et al. (2007) for move identification and Santos (1996) for the analysis of moves in order to examine common linguistic features identified in the moves that are used to serve the social and communicative purpose of conference abstracts. The findings revealed that moves 1 (situating the research), 2 (presenting the research), and 3 (describing the methodology) are frequently included in the conference abstracts, whereas moves 4 (summarizing the results) and 5 (discussing the research) can be less frequent. It is concluded that this persuasive writing genre possesses 3 obligatory or strongly prototypical moves and 2 optional ones. Finally, some pedagogical implications are derived from the findings to inform further practice with regard to teaching and learning English for Academic Purposes (EAP) in second and foreign language learning contexts.